Clinical attributes and treatment characteristics are associated with work productivity and activity impairment in people with severe haemophilia A. Issue 6 (17th July 2021) - O'Hara, Jamie; Noone, Declan; Jain, Mohit; Pedra, Gabriel; Landis, Sarah; Hawes, Charles; Burke, Tom; Camp, Charlotte
Abstract: Introduction: Few studies have examined the real‐world impact of haemophilia on daily activities and work productivity in people with severe haemophilia A (PWSHA). Aim: To determine clinical attributes and treatment characteristics associated with impairment in daily activities and work among PWSHA using the patient‐reported Work Productivity and Activity Impairment‐General Health Questionnaire (WPAI‐GH). Methods: PWSHA were asked to complete the WPAI‐GH as part of the Cost of Haemophilia in Europe: A Socioeconomic Survey (CHESS) study. Outcomes were determined for activity impairment (AI), absenteeism, presenteeism and overall work productivity loss (WPL). Descriptive statistics and regression analyses were used to evaluate the association between these outcomes and clinical and treatment attributes. Results: Overall, 376 participants completed the AI element of WPAI‐GH; 175 were employed and thus also reported on work impact. Mean ± standard deviation scores were as follows: AI = 34.2% ± 25.8%; absenteeism = 0.06% ±0.2%; presenteeism = 26.8% ± 22.4%; WPL = 28.6% ± 24.0%. Increased AI and WPL were associated with high haemophilia‐related morbidity, measured both as chronic pain ( p < .001 for both) and joint synovitis (AI: p <0.001; WPL: p = .017). In descriptive and multivariate analyses, lifelong prophylaxis was associated with reduced AI ( p < .001 and p = .031, respectively); high therapy adherence was associated with reduced AI ( p = .001 and p = .012, respectively) and with reduced WPL ( p < .001 and p = .012, respectively). Conclusion: The WPAI‐GH identified haemophilia‐related morbidity and treatment characteristics, including therapy regimen and adherence, as key attributes impacting functional impairment and work contributions of PWSHA. Early prophylactic intervention and greater adherence to therapy may lead to lower AI and WPL in PWSHA.